Endothelial Activation and Stress Index (EASIX) to predict mortality after allogeneic stem cell transplantation: A prospective study - Penack, O. (BMJ Publishing Group, 2025)
Background: We previously reported that the "Endothelial Activation and Stress Index" (EASIX; ((creatinine×lactate dehydrogenase)÷thrombocytes)) measured before start of conditioning predicts mortality after allogeneic hematopoietic stem cell transplantation (alloSCT) when used as continuous score. For broad clinical implementation, a prospectively validated EASIX-pre cut-off is needed that defines a high-risk cohort and is easy to use.
Method: In the current study, we first performed a retrospective cohort analysis in n=2022 alloSCT recipients and identified an optimal cut-off for predicting non-relapse mortality (NRM) as EASIX-pre=3. For cut-off validation, we conducted a multicenter prospective study with inclusion of n=317 first alloSCTs from peripheral blood stem cell in adult patients with acute leukemia, lymphoma or myelodysplastic syndrome/myeloproliferative neoplasms in the European Society for Blood and Marrow Transplantation network.
Results: Twenty-three % (n=74) of alloSCT recipients had EASIX-pre ≥3 taken before conditioning. NRM at 2 years was 31.1% in the high EASIX group versus 11.5% in the low EASIX group (p<0.001). Patients with high EASIX-pre also had worse 2 years overall survival (51.6% vs 70.9%; p=0.002). We were able to validate the cut-off and found that EASIX ≥3 was associated with more than twofold increased risk for NRM in multivariate analysis (HR=2.18, 95% CI 1.2 to 3.94; p=0.01). No statistically significant difference could be observed for the incidence of relapse.
Conclusions: The results of this study provide a prospectively validated standard laboratory biomarker index to estimate the transplant-related mortality risk after alloSCT. EASIX ≥3 taken before conditioning identifies a population of alloSCT recipients who have a more than twofold increased risk of treatment-related mortality.